The Effectiveness of Cognitive Behavior Therapy Group Counseling Using Problem Solving Techniques to Improve the Resilience of First-Year Students at University - Liza, Ledya Oktavia; Rusandi, M. Arli; Situmorang, Dominikus David Biondi; Ifdil, Ifdil (COUNS-EDU: The International Journal of Counseling and Education, 2023)
Students experience many problems and various demands. Especially first-year students who are just adapting to the lecture environment. For that, of course, it is necessary to prevent mental illness and increase positive things. This research aims to increase the resilience of first-year students. The research method used is a repetitive measure with a pretest and multiple posttest design with a sample of 7 people selected purposively from 19 first-year students University who have low resilience. The results of the analysis using repeated measures showed that group counseling cognitive behavior therapy using problem-solving techniques was effective in increasing resilience (F (2.12)=460.620); p<0.01).